Ultrafast ionization and fragmentation dynamics of polycyclic atomatic hydro-carbons by XUV radiation. Issue 11 (January 2020) - Manschwetus, B; Chopra, P; Tikhonov, D; Köckert, H; Gruet, S; Lahl, J; Maclot, S; Peschel, J; Steber, A L; Lee, J W L; Boll, R; Bari, S; et al.
Synopsis: In the interstellar medium polycyclic aromatic hydrocarbon molecules (PAH) are exposed to strong ionizing radation leading to complex organic photochemistry. We investigated these ultrafast fragmentation reactions after ionization of the PAHs phenanthrene, fluorene and pyrene at a wavelength of 30.3 nm using pump probe spectroscopy at a free electron laser. We observe double ionization and afterwards hydrogen abstraction and acetylene loss with characteristic time scales for the reaction processes below one hundred femtoseconds.